Remarks on Alvin Plantinga’s conception of necessity - Czernecka-Rej, Bożena (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2010)
Alvin Plantinga’s understanding of necessity is discussed. The kinds of necessity, as seen by Plantinga, are indicated, and concepts are described which are sometimes identified with the concept of necessity. The distinction between de dicto necessity and de re necessity is the principal matter for Plantinga. After their short characteristic, the attempts of the de re necessity rejection, undertaken by some authors, are presented. In the final part of the paper Plantinga’s argumentation aiming at defense of the de re necessity is discussed. Critical remarks, concerning the presented material, are a part of the paper.